Promoting Student Investigation of Local Environmental Issues through the Southern Highlands Environmental Project Project Report - Bousquet, Woodward S. (Appalachian State University, 1993)
Originally published in 1993, this report is a compilation of a survey evaluating issues with the local environment in the Southern Highlands. The report is based on a five-day teacher institute and a 1988-89 school year assessment. Teachers assisted their students in investigating environmental issues in their home communities, and helped the students share their research results through science fair projects, PTO meetings, or articles in local newspapers. Teachers submitted project reports when the environmental unit was completed, and evaluations of the teachers took place during a two-hour phone call. The report published by Bousquet includes the project description and initiative, needs assessment, teacher institute, classroom implementation, outcomes, and dissemination.